Homoeopathy and Ganglion Cyst: An Evidence-Based Clinical Case Report of Ganglion Cyst (Advancements in Homeopathic Research, 2023)
A ganglion cyst is soft tissue swelling that occurs  most commonly over the wrist and hand. Apart from  bumps, many ganglion cysts are asymptomatic.  Sometimes pain, weakness, or paraesthesia may  present. The two main concerns for patients have  been the cosmetic appearance of the cysts and the  fear of future malignant growth. Current treatment of  ganglion cysts has only options- either conservative  or surgical excision. But there is a change of  reappearance of development even after successful  surgical intervention. In homeopathy, there is ample  literature regarding ganglion cysts and encouraging  documents regarding the treatment of ganglion cysts.  Below the present case report intends to record  individualized homoeopathic constitutional medicine  that cured a ganglion cyst on the wrist. Drug selection  is exclusively based on the totality of symptoms. But  the present case report is based on a single case; it  required more extensive research and clinical studies  to improve the study outcome. [1]
Keywords: Ganglion cyst; Homoeopathy; Case Report; Nitric Acidicum